Human Nature, Cosmic Evolution and Modernity in Hölderlin - Cummins, Neil Paul (Cosmos and History: The Journal of Natural and Social Philosophy, 2007)
The German Romantic Friedrich Houml;lderlin developed a unique perspective on the relationship between humankind and the rest of nature. He believed that humanity has a positive role to play in cosmic evolution, and that modernity is the crucial stage in fulfilling this role. In this paper I will be arguing for a reinterpretation of his ideas regarding the position of humankind in cosmic evolution, and for an application of these ideas to the lsquo;environmental crisisrsquo; of modernity. This reinterpretation is significant because it entails an inversion of the conventional notion of causality in the lsquo;environmental crisisrsquo;; instead of humans lsquo;harmingrsquo; nature, in the reinterpretation it is nature that causes human suffering.